2016
DOI: 10.1016/j.jcat.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Phillips catalyst by various olefins: Stoichiometry, thermochemistry, reaction products and polymerization activity

Abstract: The adsorption, reaction and desorption of ethylene or hexenes on Cr(VI)/SiO 2 containing 1 or 3 weight% chromium was monitored by thermogravimetry, differential scanning calorimetry and mass spectrometry. Reaction of Cr(VI)/SiO 2 with ethylene at a temperature of 200 °C always included some oligomerization, making it impossible to identify the stoichiometry of the initial redox reaction. Reaction of Cr(VI)/SiO 2 with 1-hexene or cyclohexene at 150 °C indicated an adsorption stoichiometry of one olefin per chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
(34 reference statements)
2
18
0
Order By: Relevance
“…In summary, the first relevant result emerging from our spectroscopic study is the identification, during the reduction of Cr VI /SiO 2 in ethylene, of 6-fold-coordinated Cr II species in interaction with a methylformate molecule. This novel concept is in very good agreement with recent findings by McDaniel and co-workers, who demonstrated that under commercial ethylene polymerization conditions oxygenates may remain attached to the chromium sites . The next questions are whether these hindered Cr II sites are involved in ethylene polymerization and whether methylformate remains attached to the Cr sites during ethylene polymerization, participating in the whole reaction.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In summary, the first relevant result emerging from our spectroscopic study is the identification, during the reduction of Cr VI /SiO 2 in ethylene, of 6-fold-coordinated Cr II species in interaction with a methylformate molecule. This novel concept is in very good agreement with recent findings by McDaniel and co-workers, who demonstrated that under commercial ethylene polymerization conditions oxygenates may remain attached to the chromium sites . The next questions are whether these hindered Cr II sites are involved in ethylene polymerization and whether methylformate remains attached to the Cr sites during ethylene polymerization, participating in the whole reaction.…”
Section: Resultssupporting
confidence: 89%
“…Our new spectroscopic evidence reveals that the chromium site involved in ethylene polymerization is a divalent ion, 6-fold coordinated, and in interaction with an external nucleophilic ligand (mostly methylformate). This study provides the first spectroscopic identification, at the molecular level, of the oxygenated species adsorbed on the catalyst during the induction period inferred by indirect TG, DSC, and MS experiments . We also introduce the important concept that oxygenates remain in the Cr coordination sphere also during ethylene polymerization.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…At about 400 • C, the chromium is oxidized into the hexavalent form, which spreads out and becomes anchored onto the support as chromate or dichromate surface esters [3,[5][6][7][8][9][10][11][12][13][14]. These species are then reduced by ethylene to a lower valence, expanding the potential coordination sphere, alkylating the Cr, and forming the coordinatively unsaturated active sites [3][4][5][15][16][17][18][19][20]. Consequently, and somewhat unusually for inorganic industrial catalysts, the active sites are individually attached to the support.…”
Section: Introductionmentioning
confidence: 99%